Developing your counselling and psychotherapy skills and practice - Timulak, Ladislav (SAGE, 2011)
Developing Your Counselling and Psychotherapy Skills and Practice fills the void between books that cover basic counselling skills and those that cover specific methods in depth. For the trainee or clinician who asks "I am sitting in front of my client, now what do I do next?", Timulak's book will provide that answer.' Paul Jerry, Psychologist and Associate Professor, Athabasca University.